Determinants of diversity and composition of the tapeworm fauna of blue sharks, Prionace glauca: a geographical and host-specificity analysis. (7th December 2022) - Penadés-Suay, J.; Jarque-Rico, A. E.; Tomás, J.; Aznar, F. J.
Abstract: Blue sharks, Prionace glauca, are cosmopolitan, extremely vagile sharks and the species among elasmobranchs for which most surveys containing tapeworm community data are available worldwide. In this study we report on the tapeworm fauna of three samples of blue sharks ( n = 37) from two new regions (one sample from Galicia, north-east Atlantic, and two from Valencia, western Mediterranean), and compared it with previous studies, assessing the relative role of the ecological and evolutionary factors in structuring local tapeworm assemblages. Nine cestode taxa were identified, of which four included adult specimens, that is, Platybothrium auriculatum, Prosobothrium armigerum, Anthobothrium caseyi and Molicola horridus . The abundance of these species, and Brillouin's diversity index, differed significantly among samples without a clear geographical signal. A comparison with six previous surveys revealed that tapeworm assemblages were composed of the same 'core' taxa, with mean species richness typically ranging from two to four species. Global records of adult tapeworms in blue sharks included: 15 taxa identified at species level, of which only eight (generalist trypanorhynchs) were shared with other sympatric host species; five mostly with other carcharhinids; and three with large lamnid sharks sharing the blue sharks' habitat. The composition of tapeworm communities of blue sharks is thus highly constrained by strong host specificity, with composition and abundance varying across localities depending on idiosyncratic environmental conditions.